1980
DOI: 10.1177/00220345800590060501
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxic Activity in Teeth with Necrotic Pulps

Abstract: From root canals of 13 teeth with necrotic pulps, samples were taken for analysis of endotoxin content by means of the Limulus by lysate technique. The results were related to the viable bacteria count of root canal samples, phenol/water-extracted lipopolysaccharides (LPS) from different gram-negative anaerobic bacteria, and to different fractions of inflammation exudate. It was found that the endotoxic activity of the root canal samples was correlated with the presence and the number of gram-negative bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
1
4

Year Published

1981
1981
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(68 citation statements)
references
References 14 publications
(6 reference statements)
3
60
1
4
Order By: Relevance
“…More than 300 bacterial species are recognized as components of the oral microflora (Moore and Moore, 1994). However, only relatively few species appear to be able to invade the root canal space and infect the root canal (Kantz and Henry, 1974;Sundqvist, 1976;Dahlén and Bergenholtz, 1980). This suggests that many species of oral bacteria do not have the properties necessary to invade tubules and survive within the intratubular environment.…”
Section: (Iv) Microflora Of the Infected Root Canalmentioning
confidence: 99%
“…More than 300 bacterial species are recognized as components of the oral microflora (Moore and Moore, 1994). However, only relatively few species appear to be able to invade the root canal space and infect the root canal (Kantz and Henry, 1974;Sundqvist, 1976;Dahlén and Bergenholtz, 1980). This suggests that many species of oral bacteria do not have the properties necessary to invade tubules and survive within the intratubular environment.…”
Section: (Iv) Microflora Of the Infected Root Canalmentioning
confidence: 99%
“…Endotoxin content in infected root canals was higher among symptomatic teeth, teeth with radiolucent areas and with exudation than in those without these alterations 8,21 . Dahlén, Bergenholtz 6 (1980) observed that the endotoxic activity of the root canal samples was correlated with the presence and the number of Gram-negative bacteria in the root canal. Elimination of microorganisms from the root canal system has been the major goal of endodontic treatment 3 .…”
mentioning
confidence: 99%
“…2,3 Ancak, bunlardan sadece bir kısmı (150 civarında) pulpaya çeşitli yollarla (koronal, retrograd veya hematojen) girerek, pulpa hastalıklarına neden olabilmektedir. [4][5][6][7][8][9] Kök kanalındaki bu bakteriler 10-12 çeşit genustan oluşmaktadır. 7,9 Örneğin, …”
Section: Kök Kanallarında Mikroorganizmalarunclassified